Pengaruh Penambahan Bubuk Daun Murbei (Morus alba L.) Terhadap Karakteristik Marshmallow - Yunanto, Christin; Ekawati, I Gusti Ayu; Mayun Permana, I Dewa Gde (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
The purpose of this research was to know the effect of mulberry leaves powder addition on marshmallow characteristic and to determine the right amount of mulberry leaves powder addition that produced marshmallow with the best characteristics. This research used a completely randomized design with treatment consisting of 5 levels of concentration ratio of mulberry leaves powder (0%, 2%. 4%, 6%, 8%). Each treatment repeated 3 times in order to obtain 15 experimental units. The data obtained were analysed by analysis of variance and if there was an effect, then it will be followed by the Duncan Multiple Range Test (DMRT). The result showed that the addition of mulberry leaves powder had significant effect (p>0.05) on ash content, antioxidant activity, vitamin C, color intensity, color sensory, scent, texture, taste, and overall acceptance. The result showed that 4% concentration of mulberry leaves powder addition in marshmallow had significant effect on ash content, antioxidant activity, vitamin C, Color intensity, color sensory, scent, texture, taste, and overall acceptance. The 4% addition of mulberry leaves powder produced the best characteristics with 27.67% water content; 0.55% ash content; 15.82% antioxidant activity; 0.79 mg/g vitamin C; 46.30 L* score; -5.93 a* score; 20.77 b* score; color liked; scent liked; texture liked; taste liked; all acceptance liked.